Identification of Energy Saving Potential Through Energy Audit at PT. ABC - Wardhana, Alex Sandria Jaya; Damarwan, Eko Swi (DPTE FT UNY, 2023)
Increasing energy efficiency is one of the most important functions for reducing energy costs as well as production costs. One way to reduce the use of electrical energy consumption is by saving energy. This study aims to determine how much energy savings at PT ABC through an energy audit. An energy audit is carried out with two main activities, namely identifying the profile of patterns of electricity use and analysis of power quality. The results of the analysis are then expected to be the basis for knowing the potential for energy savings and energy conservation in the industry. The method used in this study begins with field observations, measurements of electrical systems, and measurements of production machines and production support equipment. Based on some data, both primary data and secondary data, an analysis is carried out through calculations to determine potential energy-saving opportunities. The main energy source used at PT. ABC is from PLN with 1 subscription to a 3-phase system with an installed power of 197 kVA. Energy use or consumption for a year is 804,279.97 kWh. Opportunities for energy savings through energy audits that have been carried out are expected to have an impact on the company, namely energy cost savings of IDR 137,344,162 per year